2023
DOI: 10.1097/gox.0000000000004873
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-scope Cosmetic Surgery: A Review of Malpractice Lawsuits against Nonplastic Surgeons

Abstract: Background: The increasing patient demand for cosmetic surgeries and minimally invasive procedures has encouraged physicians without aesthetic surgery training accredited by the American Board of Medical Specialties to provide these services. This systematic review aims to determine the rate of out-of-scope practice in medical malpractice lawsuits involving cosmetic surgery or minimally invasive procedures performed by nonplastic surgeons. Methods: Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…33 Studies have consistently shown that non-ABMS certified physicians are more commonly revoked of their licenses and provide lower quality of care when compared with ABMS-recognized board-certified physicians, hence the importance and value lended to boardcertification. 30,31,34,35 The value of board-certification as a concept is acknowledged by the vast majority of respondents in this survey; unfortunately, the ability to create and title an unaccredited "board-certification" has allowed others to take advantage of the trust built by the establishment of the ABMS, at the same time bypassing their oversight. Additionally, the news is filled with reports of postcosmetic-surgery horror stories due to non-ABPS certified surgeons performing cosmetic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Studies have consistently shown that non-ABMS certified physicians are more commonly revoked of their licenses and provide lower quality of care when compared with ABMS-recognized board-certified physicians, hence the importance and value lended to boardcertification. 30,31,34,35 The value of board-certification as a concept is acknowledged by the vast majority of respondents in this survey; unfortunately, the ability to create and title an unaccredited "board-certification" has allowed others to take advantage of the trust built by the establishment of the ABMS, at the same time bypassing their oversight. Additionally, the news is filled with reports of postcosmetic-surgery horror stories due to non-ABPS certified surgeons performing cosmetic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the news is filled with reports of postcosmetic-surgery horror stories due to non-ABPS certified surgeons performing cosmetic procedures. [6][7][8][9][10][11]35 With a high percentage of participants in this study demonstrating a significant gap in knowledge regarding the scope of plastic surgery and an even larger gap in understanding the pathways leading to board certification, there is potential for confusion as patients seek the care of plastic surgeons, not knowing whether the providers they identify are in fact true plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%